The Epidemiology and Phenotypes of Ocular Manifestations in Childhood and Juvenile Myasthenia Gravis: A Review - Heckmann, Jeannine M.; Europa, Tarin A.; Soni, Aayesha J.; Nel, Melissa (Frontiers in Neurology, 2022)
Myasthenia gravis (MG) appears to have a similar incidence among adult populations worldwide. However, epidemiological and phenotypic differences have been noted among children and juveniles with MG. We reviewed the literature on childhood- and juvenile-onset MG among different populations, with the focus on ocular involvement, antibody profiles, the genetic susceptibility to juvenile MG phenotypes, the use of immune treatments, and the reported responses of extraocular muscles to therapies. Although epidemiological studies used different methodologies, reports from Asia, compared to Europe, showed more than two-fold higher proportions of prepubertal onset (before 12 years) vs. postpubertal-onset juveniles with MG. Compared to European children, ocular MG was 4-fold more frequent among Asian children, and 2–3-fold more frequent among children with African ancestry both in prepubertal and postpubertal ages at onset. These results suggest genetic influences. In Asia, HLA-B*46 and DRB1*09 appeared overrepresented in children with ocular MG. In Europe, children with MG had a significantly higher rate of transforming from ocular to generalized disease and with an overrepresentation of HLADRB1*04. Although treatment regimens vary widely and the responses to immune therapies of the ocular muscles involved in MG were generally poorly described, there were indications that earlier use of steroid therapy may have better outcomes. Reports of treatment-resistant ophthalmoplegia may be more frequent in African and Asian juvenile MG cohorts compared to Europeans. Genetic and muscle gene expression studies point to dysregulated muscle atrophy signaling and mitochondrial metabolism pathways as pathogenetic mechanisms underpinning treatment-resistant ophthalmoplegia in susceptible individuals. In conclusion, phenotypic differences in juveniles with ocular manifestations of MG were evident in different populations suggesting pathogenetic influences. Treatment responses in MG-associated ocular disease should attract more careful descriptive reports. In MG, extraocular muscles may be vulnerable to critical periods of poor force generation and certain individuals may be particularly susceptible to developing treatment-resistant ophthalmoplegia. The development of prognostic biomarkers to identify these susceptible individuals is an unmet need.